2015
DOI: 10.1586/14737159.2015.1069184
|View full text |Cite
|
Sign up to set email alerts
|

Exact Sciences’ experience with the FDA and CMS parallel review program

Abstract: Colorectal cancer (CRC) is the third most commonly diagnosed cancer and the second leading cause of cancer death among men and women combined in the USA. Although the benefits of early CRC detection are widely recognized, screening rates are suboptimal. Cologuard is a multitarget stool DNA screening test that offers a unique non-invasive option for CRC screening. Cologuard was the first product to be reviewed under a pilot parallel review program jointly conducted by the US FDA and the Centers for Medicare & M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…SOCS3 is known to inhibit cytokine signaling via Janus kinase (JAK)/signal transducers, activators of transcription [31], NFkB, and focal adhesion kinase (FAK) signaling pathways. Substantial data demonstrate the link between SOCS3 regulation of inflammation and its suppressor activity on tumor initiation and development [11, 32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…SOCS3 is known to inhibit cytokine signaling via Janus kinase (JAK)/signal transducers, activators of transcription [31], NFkB, and focal adhesion kinase (FAK) signaling pathways. Substantial data demonstrate the link between SOCS3 regulation of inflammation and its suppressor activity on tumor initiation and development [11, 32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, only one device (Exact Sciences' Cologuard test, a multitarget stool DNA test developed for noninvasive screening for colorectal cancer) was approved through the process. The time from premarket approval submission to the final NCD was 489 days compared to an average of 612 days for other NCDs issued in 2013 (75). While this suggested that parallel-review process could shorten the expected interval from regulatory approval to coverage determination, the experience with Cologuard was only a single case.…”
Section: Parallel Submission (Review)mentioning
confidence: 97%
“…Suppressor of cytokine signaling (SOCS3) is known to inhibit cytokine signaling through Janus kinase (JAK)/signal transducers, activators of transcription [3], NFkB, and focal adhesion kinase (FAK) signaling pathways.…”
Section: Egyptian Journal Of Medical Research (Ejmr)mentioning
confidence: 99%